Meningkatkan Loyalitas melalui Citra Merek, Kepercayaan, dan Biaya Ujrah - Desy Prastyani; Muhammad Ihsan Alif (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This This study aims to better understand how to create customer loyalty to one of the existing products at the Pekalongan branch of the Sharia pawnshop using brand image, trust and cost of ujrah for gold pawn products. It can also increase customer loyalty at the Pekalongan branch of Islamic pawnshops, both new customers and customers. a long time ago. This research includes field research using a quantitative approach. This research was conducted on Pekalongan Branch Sharia Pawnshop customers using accidental sampling with a sample of 100 respondents. Data analysis technique with multiple linear analysis. The results of this study indicate that brand image has a positive effect on customer loyalty, trust has a positive effect on customer loyalty, and the cost of ujrah has a positive effect on customer loyalty. Based on the F test, it is known that the three independent variables studied simultaneously affect customer loyalty with an adjusted R Square value of 0.272. . which shows that 27.2% of the customer loyalty variable can be explained by the three independent variables, while the remaining 72.8% is influenced by other variables outside the three variables in this study.